Result of Surgery to Patients with Brain Tumor in Cienfuegos - Jorge Luis Acevedo Cardoso; Samuel Sánchez Sánchez; Yoniel Suárez Guerrero; Tamara García Alfonso de Armas; Wendy Gómez Menéndez (Revista Finlay)
Foundation: brain tumors cause high mortality, decrease in quality of life and impact negatively family health. Objective: to describe the results of surgical interventions to patients with brain tumors in Cienfuegos between January 2012 and December 2015. Methods: a cross-sectional descriptive study was carried out at the General University Hospital Dr. Gustavo Aldereguía Lima de Cienfuegos, covering the period between January 2012 and December 2015. The universe consisted of 53 patients. The variables studied were: age, sex, history of chronic diseases, history of neoplasia of another location, onset syndrome, anatomical location according to the imaging study performed, degree of macroscopic cytoreduction, Karnofsky scale, tumor type, postoperative complications and survival after six months of surgery. The analysis was based on descriptive and inferential statistics. Results: there was a slight predominance of females over males. 67.9 % of the patients did not present associated comorbidity, 45.3 % started as an endocranial hypertension syndrome, 81.9 % had supratentorial localization and 73.6 % had total macroscopic tumor cytoreduction. The most frequent histological type was astrocytoma 34 %. There was a 60.4 % survival at six months and only 6.2 % had a quality of life lower than 70 points according to the Karnofsky Scale. Conclusion: a greater survival was associated with meningothelial meningioma, emphasizing lethality in grade IV astrocytomas and lung metastasis. The most frequent and associated mortality complication was postoperative neurological deterioration.